2011
DOI: 10.3109/00365513.2010.548875
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperbaric oxygen and medical ozone therapies in a rat model of experimental distal colitis

Abstract: Our data showed that the therapeutic effect of OT is more pronounced than that of HBO therapy. Its possible effect is by means of decreasing inflammation, edema, and oxidative stress. These findings also suggest that it is possible to improve the outcome of ADC by using ozone therapy as an adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…31,33 Recently, we have reported that OT has a preventive effect in the intestine and esophagus by decreasing tissue damage and increasing the antioxidant enzyme activity in experimental model of distal colitis, necrotizing enterocolitis, caustic esophageal burn model, acute necrotizing pancreatitis, and acetaminopheninduced nephrotoxicity. 20,[34][35][36][37][38] In conclusion, our data suggest that OT might protect kidneys against IRI by modulating a moderate oxidative and nitrosative stress, which, in turn, increases the antioxidant endogenous systems.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…31,33 Recently, we have reported that OT has a preventive effect in the intestine and esophagus by decreasing tissue damage and increasing the antioxidant enzyme activity in experimental model of distal colitis, necrotizing enterocolitis, caustic esophageal burn model, acute necrotizing pancreatitis, and acetaminopheninduced nephrotoxicity. 20,[34][35][36][37][38] In conclusion, our data suggest that OT might protect kidneys against IRI by modulating a moderate oxidative and nitrosative stress, which, in turn, increases the antioxidant endogenous systems.…”
Section: Discussionmentioning
confidence: 90%
“…Protein carbonyl content (PCC) using the method of Levine et al as has already been described in our previous works. 4,5,8,20,21 Samples were analyzed for their nitrate plus nitrite (NO x ) concentrations, end products of nitric oxide degradation, by using ion chromatography (Dionex ICS -1000, Sunnyvale, CA, USA). The supernatant of the tissues was filtered using 22-nm injector filters (Sartorius Minisart, Goettingen, Germany).…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Most studies were published in Turkey except for two studies published in the United States [63,66] and one in Israel [64]. Several studies reported that HBOT reduced markers of inflammation, including TNF-alpha [61,63,66], IL-1β [63,66] and neopterin levels [56]. HBOT also decreased edema or colonic tissue weight in 4 studies [56,57,62,64].…”
Section: Resultsmentioning
confidence: 99%
“…Ozone theraphy had an improving effect on oxidant/antioxidant status and a healing effect on the histopathological changes of tissues with acute distal colitis 26 . Ozone administration significantly reduced the severity of ADC in rats.…”
Section: Discussionmentioning
confidence: 99%